Klinefelter syndrome: clinical and auxological features of 14 patients diagnosed in childhood - M.F. Messina; D. Corica; S. Santucci; E. Pitrolo; M. Romeo; F. De Luca (PAGEPress Publications, 2013)
Klinefelter syndrome (KS) is the most frequent chromosomal aneuploidy with a prevalence of 1: 500 men but it often remains a largely undiagnosed condition and only 10% of cases are identified in childhood and adolescence. We report the anamnestic, clinical and auxological findings of 14 KS patients diagnosed in paediatric age. 3/14 patients (21%) with KS were diagnosed in prenatal age by amniocentesis, 1 patient was diagnosed at birth due to genital ambiguity and the remaining 10/14 (71.4%) were diagnosed at a chronological age younger than 15 years old for a clinical picture characterized by a peculiar cognitive and behavioral pattern or genital anomalies and abnormalities of pubertal development. The classical karyotype 47 XXY was present in 10/14 subjects (72%), a mosaic form (46 XY/47 XXY) was present in 2/14 (14%) and a complex aneuploidy (48 XXYY and 48 XXXY) was present in the remaining 2/14 (14%) patients. All KS patients diagnosed in childhood and adolescence (10/14 =71.4 %) showed a stature taller than the respective target height and also the predicted final height (calculated from a chronological age older than 7 years old) and the reached final height were significantly taller than target height. Conclusion: according to our retrospective data we can assert that KS in paediatric age is characterized by a stature taller than target height, often associated with a characteristic cognitive and behavioral pattern while the typical clinical signs and symptoms of KS are lacking and manifest only in late adolescence or adulthood.